Diversity of Essential oils in Sop Cop Nature Reserve in Sơn La province - Thi Lien, Vu; Thi Quyen, Nguyen; Huu Thu, Do (VNU Journal of Science: Natural Sciences and Technology, 2019)
According the  results of the plant species for essential oil in Sop Cop Nature Reserve  Area have identified 228 species, 158 genus of 66 families belong Pinophyta and Magnoliophyta. The diversity of essential oils plants fully expressed in 5 life forms with the spectrum of life forms is: SB = 59,65Ph + 13,59 Th + 11,40Cr + 7,89 Ch + 7,44Hm. In addition to the value for essential oils, the species also give other uses such as medicine with 228 species, edible with 64 species, timber with 62 species, making wine yeast with 27 species, spices with 25 species, making bonsai 9 species, making flavor 5 species, 3 species of oil, and lowest with 2 species having poisonous. We have been identified 16 species of plants (accounting for 7.02%) as being endangered in Vietnam Red Book (2007) and 1 species in red list of IUCN (2017). These are species with a small number of individuals that need to have policies for conservation and development Keywords  Essential oil plats, life form, plants, Sop Cop nature reserve. References [1] FAO/WHO, Guidelines for the Evaluation of Probiotics in Food, Joint FAO/WHO Working Group Report on Drafting Guidelines for the Evaluation of Probiotics in Food London, Ontario, Canada, April 30 and May 1, 2002. [2] J. Park, M.H. Floch, Prebiotics, probiotics, and dietary fiber in gastrointestinal disease, Gastroenterology Clinics of North America, 36 (2007) 47-63. https://doi.org/10.1016/j.gtc.2007. 03.001. [3] F. Mansour-Ghanaei, N. Dehbashi, K. Yazdanparast, A Shafaghi, Efficacy of Saccharomyces boulardii with antibiotics in acute amoebiasis, World Journal of Gastroenterology, 9(2003)1832-1833. https:// dx.doi.org/10.3748/ wjg.v9.i8.1832. [4] I. Castagliuolo, M.F. Riegler, L. Valenick, J.T. LaMont, C. Pothoulakis, Saccharomyces boulardii protease inhibits the effects of Clostridium difficile toxins A and B in human colonic mucosa, Infection and Immunity, 67, 1(1999)302-307. [5] A. Qamar, S. Aboudola, M. Warny, P. Michetti, C. Pothoulakis, J.T. LaMont, C.P. Kelly, Saccharomyces boulardii stimulates intestinal immunoglobulin A immune response to Clostridium difficile toxin A in mice, Infection and Immunity, 69 (2001) 2762-2765. https:// doi.org/10.1128/IAI.69.4.2762-2765.2001. [6] T.S. Chin, N.Z. Othman, R. A. Malek, N. Elmarzugi, O. M. Leng, S. Ramli, N. F. Musa, R. Aziz and H. El Enshasy, Bioprocess optimization for biomass production of probiotics yeast Saccharomyces boulardii in semi-industrial scale, Journal of Chemical and Pharmaceutical Research, 7, 3(2015)122-132. [7] D.T.N. Diep, P. George, E. Gorczyca, S. Kasapis, Studies on the viability of Saccharomyces boulardii within microcapsules in relation to the thermomechanical properties of wheyprotein. Food Hydrocolloids, 42 (2014) 232-238. https:// doi.org/10.1016/j.foodhyd.2013.07.024. [8] G.L. Miller, Use of dinitrosalicylic acid reagent for determination of reducing sugar. Analytical Chemistry, 31 (1959) 426-428 https://doi.org/ 10.1021/ac60147a030. [9] H. A. El-Enshasy and A. A. El-Shereef, Optimization of high cell density cultivation of (Probiotic/Biotherapeutic) yeast Saccharomyces boulardii adapted to dryness stress, Deutsche Lebensmittel-Rundschau 104,93(2008)89-394. [10] K. Rajkowska, A. K.-S. Bska and A. Rygala, Probiotic activity of Saccharomyces cerevisiae var.boulardii against human pathogens, Food Technology and Biotechnology, 50, 2 (2012) 230–236. [11] R. Zbinden, E.E. Gonczi, M. Altwegg, Inhibition of Saccharomyces boulardii (nom. inval.) on cell invasion of Salmonella typhimurium and Yersinia enterocolitica, Microbial Ecology in Health and Disease, 11(1999)158–162. https://doi.org/10. 1080/089106099435736. [12] D. Czerucka, T. Piche, P. Rampal, Review article: Yeasts as probiotics – Saccharomyces boulardii, Alimentary Pharmacology Therapeutics, 26(2007)767–778. https://doi.org/10.1111/j.1365 -2036.2007.03442.x. [13] L.V. Mc Farland, P. Bernacoscani, Saccharomyces boulardii. A Review of an Innovative Biotherapeutic Agent, Microbial Ecology in Health and Disease, 6(1993)157-171. https://doi. org/10.3109/08910609309141323. [14] K. Rajkowska and A. Kunicka-Styczynska, Probiotic properties of yeasts isolated from chicken feces and kefirs, Polish Journal of Microbiology, 59,4(2010) 257-263. [15] J.L.R. Fietto R.S. Araujo and F.N. Valadao, Molecular and physiological comparisons between Saccharomy cescerevisiae and Saccharomyces boulardii, Canadian Journal of Microbiology, 50 (2004) 615–621. https://doi. org/10.1139/w04-050. [16] J.L. Muller, K.L. Protti, M.S. Machado, L.L.V. Lacerda, T.M.B. Bresolin, P.S. Podlech, Comparison of Saccharomyces boulardii growth in an air-lift fermentor and in a shaker, Ciência e Tecnologia de Alimentos, 27,4(2007)688-693. http://dx.doi.org/10.1590/S0101-206120070004 00003.